Data Reduction of Laser Ablation Split‐Stream (LASS) Analyses Using Newly Developed Features Within Iolite: With Applications to Lu‐Hf + U‐Pb in Detrital Zircon and Sm‐Nd +U‐Pb in Igneous Monazite. (26th December 2017) - Fisher, Christopher M.; Paton, Chad; Pearson, D. Graham; Sarkar, Chiranjeeb; Luo, Yan; Tersmette, Daniel B.; Chacko, Thomas
Abstract: A robust platform to view and integrate multiple data sets collected simultaneously is required to realize the utility and potential of the Laser Ablation Split‐Stream (LASS) method. This capability, until now, has been unavailable and practitioners have had to laboriously process each data set separately, making it challenging to take full advantage of the benefits of LASS. We describe a new program for handling multiple mass spectrometric data sets collected simultaneously, designed specifically for the LASS technique, by which a laser aerosol is been split into two or more separate "streams" to be measured on separate mass spectrometers. New features within Iolite (https://iolite-software.com ) enable the capability of loading, synchronizing, viewing, and reducing two or more data sets acquired simultaneously, as multiple DRSs (data reduction schemes) can be run concurrently. While this version of Iolite accommodates any combination of simultaneously collected mass spectrometer data, we demonstrate the utility using case studies where U‐Pb and Lu‐Hf isotope composition of zircon, and U‐Pb and Sm‐Nd isotope composition of monazite were analyzed simultaneously, in crystals showing complex isotopic zonation. These studies demonstrate the importance of being able to view and integrate simultaneously acquired data sets, especially for samples with complicated zoning and decoupled isotope systematics, in order to extract accurate and geologically meaningful isotopic and compositional data. This contribution provides instructions and examples for handling simultaneously collected laser ablation data. An instructional video is also provided. The updated Iolite software will help to fully develop the applications of both LASS and multi‐instrument mass spectrometric measurement capabilities. Plain Language Summary: A robust platform to view and integrate multiple data sets collected simultaneously is required to realize the utility and potential of the Laser Ablation Split‐Stream (LASS) method. This capability, until now, has been unavailable and most practitioners have had to laboriously process each data set separately, making it challenging to take full advantage of the benefits of LASS. This contribution describes a new data reduction program for handling multiple time‐resolved mass spectrometric data sets collected simultaneously, designed specifically for the LASS technique, where a laser aerosol has been split into two or more separate streams. Newly developed features within Iolite enable the capability of loading, synchronizing, viewing, and reducing two or more data sets acquired simultaneously, as well as being able to run multiple DRSs (data reduction schemes) concurrently. This powerful method is now gaining momentum in the Earth Sciences, and powerful software to handle such data is long overdue. We demonstrate the utility of this new software using case studies involving Lu‐Hf and U‐Pb in detrital zircon, and Sm‐Nd and U‐Pb in igneous monazite. Key Points: We introduce a new version of Iolite with capabilities of handling multi‐stream laser ablation data This updated version of Iolite allows simultaneous viewing and data reduction of all data from each mass spectrometer We present a flexible approach where any two or more data reduction schemes (DRS) can be run simultaneously